Assembly‐free metagenomic analysis reveals new metabolic capabilities in surface ocean bacterioplankton. Issue 5 (16th May 2013) - Luo, Haiwei; Moran, Mary Ann
Summary: Uncovering the metabolic capabilities of microbes is key to understanding global energy flux and nutrient transformations. Since the vast majority of environmental microorganisms are uncultured, metagenomics has become an important tool to genotype the microbial community. This study uses a recently developed computational method to confidently assign metagenomic reads to microbial clades without the requirement of metagenome assembly by comparing the evolutionary pattern of nucleotide sequences at non‐synonymous sites between metagenomic and orthologous reference genes. We found evidence for new, ecologically relevant metabolic pathways in several lineages of surface ocean bacterioplankton using the Global Ocean Survey (GOS) metagenomic data, including assimilatory sulfate reduction and alkaline phosphatase capabilities in the alphaproteobacterial SAR11 clade, and proteorhodopsin‐like genes in the cyanobacterial genus Prochlorococcus . These findings raise new hypotheses about microbial roles in energy flux and organic matter transformation in the ocean.